PENERAPAN METODE DISCOVERY LEARNING PADA PEMBELAJARAN MENULIS TEKS ANEKDOT - Neni Triyani; Saeful Romdon; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
In this research the aim to describe of to know the students in teaching writing anecdote text using discovery learning at SMKN 1 Rengasdengklok. The research used experimental method one group pretest-postest design. The population of this research was taken from second-grade students of SMKN 1 Rengasdengklok. While the sample was 25 students of class X TKR 3, the instrument used in this research was tested pretest and posttest and lesson plan of teaching material. Data analysis show that the result of this research is the mean of pretest was 39, 32 and after students got the treatment mean of posttest was 70,46. The result of this research the students teaching writing anecdote text increase of 31.14. whilethgeresult of T-sig was (2-tailed) 0,000. Based on the data above, the hypothesis in this research was accepted, because the mean of posttest was higher than a mean of the pretest. It is concluded that discovery learning method improves students writing anecdote text at SMKN 1 Rengasdengklok.